2013
DOI: 10.1159/000354516
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Curcumin Ameliorates Aging-Related Cerebrovascular Dysfunction through the AMPK/Uncoupling Protein 2 Pathway

Abstract: Background/Aims: Age-related cerebrovascular dysfunction contributes to stroke, cerebral amyloid angiopathy, cognitive decline and neurodegenerative diseases. One pathogenic mechanism underlying this effect is increased oxidative stress. Up-regulation of mitochondrial uncoupling protein 2 (UCP2) plays a crucial role in regulating reactive oxygen species (ROS) production. Dietary patterns are widely recognized as contributors to cardiovascular and cerebrovascular disease. In this study, we tested the hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 38 publications
4
47
0
Order By: Relevance
“…The latter, a naturally occurring polyphenol from the plant Curcuma longa, AMPK/PPARa/UCP2 and renal damage in hypertension has been shown to significantly decrease ROS production and improve cerebrovascular endotheliumdependent relaxation in aging rats [47]. Similarly to our results, curcumin administration increased cerebrovascular AMPK phosphorylation and UCP2 levels both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The latter, a naturally occurring polyphenol from the plant Curcuma longa, AMPK/PPARa/UCP2 and renal damage in hypertension has been shown to significantly decrease ROS production and improve cerebrovascular endotheliumdependent relaxation in aging rats [47]. Similarly to our results, curcumin administration increased cerebrovascular AMPK phosphorylation and UCP2 levels both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the properties of B. oleracea outlined in our experimental context appear to be quite similar to those described for curcumin [47]. The latter, a naturally occurring polyphenol from the plant Curcuma longa, AMPK/PPARa/UCP2 and renal damage in hypertension has been shown to significantly decrease ROS production and improve cerebrovascular endotheliumdependent relaxation in aging rats [47].…”
Section: Discussionsupporting
confidence: 71%
“…Curcumin promoted eNOS activity in cultured endothelial cells or in vivo rats that ameliorated aging-related cerebrovascular dysfunction. 40 Cadmium-induced vascular dysfunction and hypertension in mice are effectively attenuated by curcumin treatment in which increased eNOS expression is involved. 27 Boonla et al 41 have demonstrated that curcumin improves vascular remodeling and endothelial dysfunction in hypertensive rats associated with an upregulation of eNOS.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, which is termed as 1,7-bis(4-hydroxy-3-m e t h o x y p h e n y l ) -1 , 6 -h e p a t a d i e n e -3 , 5 -d i o n e , o r diferulolylmethane, is a major constituent of the yellow spice turmeric that is extracted from the rhizome of the plant Curcuma longa [9][10][11][12][13]. Curcumin has been shown of anticancer effects in a number of cancers, including PC [9,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%